Identifikasi Mineral Lokal Batu Gayo, Aceh dan pemanfaatannya Sebagai massa raga keramik Stoneware - effendi, mochammad dachyar; Cingah, Made; supriyadi, supriyadi (JST (Jurnal Sains dan Teknologi), 2018)
Indonesia is known to have abundant mineral resources and some of them have not been properly utilized. Frozen rock from Gayo area, Aceh is suspected to have a feldspar content that can be used as a raw material for the manufacture of ceramics. This study is intended to determine the content of Gayo rocks and their compatibility as ceramic materials. For that purpose, has been identified the existing mineral content in these rocks and then made the composition of stoneware ceramic raw materials with triaxial blend Â method. different sintering temperature (800, 900, 1000, 1100 and 1250 oC respectively) has been conducted to known the efffect of sintering temperature on ceramic body. From the experiment, it is known that Gayo stone contains 69%of feldspar with specific gravity is 2.6963 + 0.1290 gram / cm3. In the sample test, the results obtained at the sintering temperature of 1250oC achieved 1.09% water absorption, a number which is included in the water impregnation area for stoneware ceramics according to the provisions of ISO 10543-3 / ASTM C373 ie <3%, .The prototype of ceramic objects made with rotary technique showing good quality (not cracked, shapedo not change, solid ceramic body